2018
DOI: 10.4174/astr.2018.95.4.222
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of dynamic risk stratification in pediatric patients with differentiated thyroid carcinoma

Abstract: PurposeRecently, the American Thyroid Association (ATA) dynamic risk stratification (DRS) has been verified to be more valuable than the static anatomical staging system for predicting prognosis in patients with differentiated thyroid carcinoma (DTC). The purpose of this retrospective study was to compare the clinical usefulness of DRS, which is based on the response to initial treatment, with that of ATA initial risk stratification in pediatric patients.MethodsA total of 144 pediatric patients underwent thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Instead, the role of sTg in DTC pediatric patients remains to be fully established [12][13][14][15]. At the same time, the usefulness of ATA risk classification in children with DTC has been evaluated in few studies [16][17][18][19][20][21], and also the 1-year response to initial therapy categories presented in the 2015 adults' guideline (i.e., excellent response, biochemical incomplete response, structural incomplete response and indeterminate response) [3] has been tested few cases of pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the role of sTg in DTC pediatric patients remains to be fully established [12][13][14][15]. At the same time, the usefulness of ATA risk classification in children with DTC has been evaluated in few studies [16][17][18][19][20][21], and also the 1-year response to initial therapy categories presented in the 2015 adults' guideline (i.e., excellent response, biochemical incomplete response, structural incomplete response and indeterminate response) [3] has been tested few cases of pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…In our series, this male preponderance may be explained by the higher frequency of metastases at diagnosis in males (p=0.036). The presence of nodal disease has been associated with persistent disease in other studies [ 5 , 7 ], and Pires et al [ 10 ] also found that female gender and distant metastasis were significantly associated with disease-free status. Of note, ATA risk group stratification and DRS were two other factors significantly associated with persistent disease, confirming the findings of others [ 4 ].…”
Section: Discussionmentioning
confidence: 90%
“…Around 60% of our patients with pulmonary metastases had regionally extensive disease, a finding supported by others [ 3 ], emphasizing the potential role of lymph node status at diagnosis for the prognosis. The DRS system was evaluated in pediatric patients by others [ 4 - 7 , 10 ]: Sung et al [ 7 ] found that both ATA risk stratification and DRS systems were associated with the clinical outcomes (p<0.001 for both); Zanella et al [ 4 ] showed that DRS was an excellent tool for predicting clinical outcomes in their cohort of sixty-six patients, in which the majority remained in the same category they had in DRS; Kim et al [ 5 ] (128 patients) compared ATA risk stratification and DRS system and demonstrated the superiority of the latter in predicting disease outcomes, similarly to Adjari et al [ 10 ] and Lazar et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 30 31 32 33 34 Kim et al applied the adults DRS system in their pediatric DTC population and concluded that DRS from 1 to 2 years after diagnosis can provide useful prognostic information along with ATA risk stratification in pediatric patients with DTC. 35 Considering these observations, we assessed the response after 1.5 years of diagnosis by taking a cutoff value of 10 ng/dL (stimulated) and 1 ng/dL (unstimulated) for classifying “responders” and “incomplete responders.”…”
Section: Dynamic Risk Stratification By Response To Treatment Reclass...mentioning
confidence: 99%